Idiopathic localised involutional lipoatrophy in a child involving multiple sites - V. P. S., Nithya; Rai, Reena; G., Umamaheswari (International Journal of Research in Dermatology, 2021)
Idiopathic localized involutional lipoatrophy (ILIL) is a rare form of localized lipoatrophy that arises spontaneously without inflammation.